CD4+ and CD8+ Regulatory T Cells in Chronic Rhinosinusitis Mucosa. Issue 2 (March 2014) - Pant, Harshita; Hughes, Amy; Schembri, Mark; Miljkovic, Dijana; Krumbiegel, Doreen
Background: Chronic rhinosinusitis (CRS) mucosal inflammation is characterized by an accumulation of effector–memory T cells, but their immune regulatory potential has not been adequately examined. Coexpression of transcription factor, forkhead box P3 (Foxp3), an interleukin-2 receptor, CD25, in CD4 + and CD8 + T cells is linked with regulatory function in humans. The aim of this study was to investigate the regulatory ell (T phenotype of CD4 + (CD4Treg) and CD8 + (CD8Treg) T cells in peripheral blood (PB) and sinus mucosa of CRS patients. Methods: Prospective study was performed involving 32 CRS with nasal polyp (CRSwNP), 14 CRS without nasal polyp (CRSsNP), and 8 control patients. Sinus and PB T lymphocytes were stained with CD3, CD4, CD8, CD25, and Foxp3 and analyzed using flow cytometry. Relevant clinical characteristics, sinus bacterial culture results, and eosinophilic mucus were examined. Results: Sinus mucosa had a higher percentage of CD4Treg (CD3 + CD4 + CD25 + Foxp3 + ) population compared with PB all patients. The percentage of PB CD4Treg and CD8Treg (CD3 + CD8 + CD25 + Foxp3 + ) was not significantly different between the study groups. CRS mucosal tissue had a higher percentage of CD4Treg and activated T-helper cells than controls. There was no significant difference in PB and mucosal CD4Treg populations in CRS patients based on the presence of allergy, sinus culture results, or eosinophilic mucus. In controls creased mucosal CD4Treg correlated with coexisting allergy. Although overall CD4Treg numbers were higher, the regulatory potential of activated CD4 + T cells (CD4Treg/activated T-helper cell ratio) was significantly lower in CRS mucosa compared with controls. The CD8Treg subset was also significantly reduced in CRSwNP mucosa compared with controls. Conclusion: A higher percentage of CD4Treg and activated T-helper cells in CRS mucosa suggests increased inflammation in CRS, independent of the presence of allergy, microbial culture results, or eosinophilic mucus. How, the decreased ratio of CD4Treg versus activated T-helper cells in CRS and reduced CD8Treg population in CRSwNPs indicates an inflammatory bias and the inability to control mucosal disease.